Feasibility of integrated high‐wavenumber Raman imaging and fingerprint Raman spectroscopy for fast margin assessment in breast cancer surgery. (30th June 2020) - Liao, Zhiyu; Lizio, Maria Giovanna; Corden, Christopher; Khout, Hazem; Rakha, Emad; Notingher, Ioan
Abstract: Intraoperative assessment of surgical margins remains one of the main challenges in cancer surgery. Raman spectroscopy can detect cancer cells with high accuracy, but it is time‐consuming. In this paper, we investigated a selective‐sampling Raman spectroscopy approach, based on high wavenumber (HW) Raman imaging (spectral range 2, 500–3, 500 cm −1 ) and fingerprint Raman spectroscopy (spectral range 600–1, 800 cm −1 ), to reduce the overall tissue analysis time while maintaining high diagnostic accuracy. HW Raman mapping was used as a first step to identify the adipose tissue regions based on the C–H stretching bands at 2, 700–2, 950 cm −1 . As residual tumors are typically found in nonadipose tissue, an algorithm was developed to allocate sampling points for fingerprint Raman spectroscopy at locations corresponding to low intensity in the HW‐Raman maps. Preliminary results show that HW‐Raman imaging based on a 671 nm laser is effective and fast for mapping of adipose tissue in breast resections, with typical imaging times of 2 min for tissue areas as large as 2 × 2 cm 2 areas. Albeit the remaining high fluorescence background in the fingerprint region prevents the use of single 671‐nm laser, the HW Raman imaging can be still exploited in combination with 785‐nm excitation Raman spectroscopy for identifying residual tumor. Although this study demonstrates the feasibility of this approach, further improvements, such as using single element detectors for HW Raman imaging, are required to increase the analysis speed further towards intraoperative use in the routine clinical setting. Abstract : Sequential high‐wave number Raman imaging and fingerprint Raman classification are used to speed up the analysis of breast cancer excisions.